Islamisasi di Nusantara Abad Ke-17 Perspektif Sea Power: Historiografi Malaka, Solor dan Mataram - Ghozali, Moh_Yusni (Historia Madania: Jurnal Ilmu Sejarah, 2025)
Specifically, this study seeks to break down the strategy of Islamization in the archipelago from the aspect of sea power (port potential). The theme of sea power was targeted in the study as a factor of Islamization because the 17th century Muslim traders experienced a heyday in the archipelago. Several studies have examined Islamization in the archipelago sourced from the coast. But, it has not explicitly mentioned the potential power played by ulama or umara in the Islamization strategy. The topic raised in this study is the Islamization of Malacca, Solor, and Mataram viewed from the perspective of sea power. The discourse raised is the strategy of Islamization of various potential aspects contained in the port such as political, social, cultural and economic aspects. The theory used to see multicausal in the process of Islamization is the theory of history. This study concludes that the pattern of cultural power built by Malacca is to build collaboration between Islamic law and customary law. Meanwhile, economic power is built by introducing muamalah Islam through symbols of fair and harmless policies. Mataram in terms of Islamization, bringing together Islamic students on the coast and Islamic Kejawen, through cultural policies (culture power). Meanwhile, Solor is more dominant in using political power through indigenization where Islamization is carried out by building an Islamic sultanate to accommodate the anti-colonial attitude of the local community. Furthermore, Islamization studies on more specific aspects are very meaningful for the development of Islamic historiography of the archipelago.